2021
DOI: 10.3892/mmr.2021.12325
|View full text |Cite|
|
Sign up to set email alerts
|

Galectin‑3 blockade suppresses the growth of cetuximab‑resistant human oral squamous cell carcinoma

Abstract: oral squamous cell carcinoma (oScc) is a cancer associated with high mortality (accounting for 3.1/100,000 deaths per year in Brazil in 2013) and a high frequency of amplification in the expression of the epidermal growth factor receptor (EGFR). Treatment with the EGFR inhibitor cetuximab leads to drug resistance in patients with oScc due to unknown mechanisms. Galectin-3 (Gal-3) is a β-galactoside binding lectin that regulates multiple signaling pathways in cells. The present study aimed to investigate the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…This could impact recognition of these HNSCC cell surface glycoproteins by Galectins, given that α2-3 NeuAc carrying LacNAc epitopes can be recognised by Galectin 1 and 3, while the α2-6 NeuAc capping blocks this recognition [47]. In oral squamous cell carcinoma (OSCC), inhibition of Galectin-3 has been shown to overcome cetuximab-resistance in murine animal models [48]. Yin et al showed that in cetuximab-resistant OSCC tumours, increased expression of Galectin-3, p-ERK1/2 and p-Akt was observed.…”
Section: Discussionmentioning
confidence: 99%
“…This could impact recognition of these HNSCC cell surface glycoproteins by Galectins, given that α2-3 NeuAc carrying LacNAc epitopes can be recognised by Galectin 1 and 3, while the α2-6 NeuAc capping blocks this recognition [47]. In oral squamous cell carcinoma (OSCC), inhibition of Galectin-3 has been shown to overcome cetuximab-resistance in murine animal models [48]. Yin et al showed that in cetuximab-resistant OSCC tumours, increased expression of Galectin-3, p-ERK1/2 and p-Akt was observed.…”
Section: Discussionmentioning
confidence: 99%
“…However, the application of cetuximab still has certain difficulties including mutations, toxicity/side effects, drug resistance and an optimal dosage to administer (35)(36)(37)(38). Furthermore, EGFR level detection needs to be performed prior to the administration of cetuximab.…”
Section: Discussionmentioning
confidence: 99%
“…These findings were realized by significant different GIII and GII (p-value = 0.002), and extremely significant difference between GIV and GII (p-value <0.001), this is in line with other studies. (77)(78)(79) This could explain as cetuximab blocked the activity of EGFR in cells that had a lot of EGFR auto-phosphorylation at the start of the cell, even though the cells did not have a lot of EGFR expression. EGFR signaling and how well EGFR suppression works are also based on other factors, like EGFR mutations and polymorphisms in the downstream pathways.…”
Section: Discussionmentioning
confidence: 99%